Medial Hypertrophy of the Ovarian Vein: A Novel Type of Vascular Pathology Associated With a Primary Ovarian Carcinoid Tumor. (January 2015) - Dessauvagie, Benjamin F.; Lai, Patrick H.; Oost, Ebo; Thomas, Anitha; Stewart, Colin J. R.
Abstract : Primary carcinoid tumors of the ovary are rare accounting for only 1% of neoplasms that are associated with the carcinoid syndrome. However, the carcinoid syndrome can occur in the absence of hepatic metastases due to the release of vasoactive peptides directly into the systemic circulation via the ovarian vein. We present a 69-yr-old woman presenting with carcinoid valvular disease and congestive cardiac failure who was found to have a primary left ovarian carcinoid tumor. At operation it was noted that the left ovarian vein had an unusually firm and thickened appearance, and histologic examination revealed marked fibromuscular medial hypertrophy with luminal compression. There was no associated vascular elastosis. This ovarian venous alteration appears to represent a novel addition to the spectrum of cardiovascular injuries associated with carcinoid tumors.